Assessing the efficacy of polyaluminium chlorides in improving pool water quality using impedance spectroscopy - A. Mortadi; E. El Hafidi; H. Nasrellah; R. Mghaiouini; E. Chahid; M. Monkade; R. El moznine (Results in Engineering, 2024)
This paper describes an experimental study on the effects of polyaluminium chloride (PAC) on pH, turbidity, and electrical properties of pool water. Our results demonstrates that as the concentration of PAC increases, pH decreases until a concentration of 2.5 mg/L, suggesting an acidic effect of the flocculant. Thus, the turbidity decreases with increasing PAC concentration up to 2.5 mg/L, indicating effective particle clumping and settling. Beyond this concentration, turbidity starts to increase, possibly due to excessive flocculant dosage or unintended reactions. Impedance spectroscopy is used to analyze the electrical properties of the treated water. The Nyquist and Bode plots reveal two relaxation processes and changes in conductivity. The optimal PAC concentration for treating pool water is found to be 2.5 mg/L, where suspended particles are effectively removed while maintaining suitable conductivity. Also, an equivalent circuit is devlopped to model the electrical behavior, and its simulation closely matches experimental data. The relaxation times and DC conductivity are influenced by the PAC concentration, with different behaviors observed below and above 2.5 mg/L. Below this concentration, PAC neutralizes particles, while above it, excess PAC content leads to increases in these parameters.